USING PERFORMANCE-BASED PEDAGOGY TO DEVELOP CRITICAL THINKING WITH SHAKESPEAREAN SONNETS IN PHILOLOGY - Lobar Alisherovna Yusupbayeva (Bright Mind Publishing, 2025)
This article highlights the effectiveness of text creation based on pictures in developing the speech skills of primary school students. Picture-based assignments help expand children's imagination, enrich their vocabulary, and foster creative thinking abilities.
Keywords: Primary school, text creation based on pictures, speech development, thinking, pedagogical competence.